Process Modeling of Mineral Dissolution From Nano‐Scale Surface Topography Observations - Starnoni, M.; Sanchez‐Vila, X.; Recalcati, C.; Riva, M.; Guadagnini, A. (Geophysical research letters, 2024)
We present an innovative approach that combines a unique real‐time data set documenting absolute dissolution rates of a calcite crystal with an original reactive transport model tailored to the analysis of the dynamics of nano‐scale mineral dissolution processes. Providing robust and physically based fundamental understanding on the kinetics of mineral dissolution is at the core of various geo‐engineered strategies to quantify chemical weathering patterns across diverse spatial and temporal scales. Here, we rely on data obtained through Atomic Force Microscopy. We provide a mathematical framework to describe three‐dimensional dynamics of the mineral surface topography, and show convergence of the numerical approach for vertical grid spacing down to sub‐nm resolution. Plain Language Summary We focus on some fundamental aspects related to modeling of mechanisms underpinning chemical weathering of minerals. The latter is a ubiquitously active phenomenon driving the Earth system evolution. It underpins a variety of physico‐chemical processes that are at the core of various geo‐engineered strategies for sustainable development, including the assessment of the role of underground storage of carbon dioxide or geothermal energy in environmental stewardship. Here, we propose an innovative approach that combines for the first time a reactive transport model with a unique real‐time data set documenting absolute calcite dissolution rates. Experimental observations correspond to high‐resolution (i.e., horizontal and vertical resolution of 19.5 and ∼0.1 nm, respectively) in‐situ Atomic Force Microscopy data obtained across a calcite sample subject to dissolution. Our original reactive transport model is designed to assist quantitative appraisal of the ensuing mineral surface topography. To combine these two powerful techniques, we provide a mathematical framework for the representation of the evolution (in space and time) of the mineral surface topography, and document the robustness of the numerical approach through a convergence analysis for vertical grid spacing down to sub‐nm resolution. Key Points We propose a novel combination of an original reactive transport model with a unique data set documenting absolute calcite dissolution rates We provide a sound mathematical framework to describe three‐dimensional dynamics of mineral surface topography We document convergence of the numerical approach for vertical grid spacing down to sub‐nm resolution